Analisis Pengaruh Motivasi Belajar, Keaktifan Mahasiswa dan Kompetensi Dosen Terhadap Prestasi Belajar dengan Metode SEM-PLS - Meliana, Dita; Armenia, Ivan Gustra Manca; Hasibuan, Sawarni (Universitas Mercu Buana, 2023)
The main goal of education is to provide people with access to the knowledge and skills they need to deal with life's difficulties. Many academic fields, including science, mathematics, and foreign languages. The motivation of students involved in educational activities comes from their own desires. Meanwhile students are more involved in their learning when they actively participate in class activities, discussions, and homework provided. Lecturer competence refers to the knowledge, skills, and capacity of effective subject communication. The problem of this research is whether there is influence from learning motivation and student activity as well as lecturer competence on student achievement. The purpose of this study was to analyze the influence of learning motivation, student activity and lecturer competence on student achievement. This study uses an explanatory survey research method. The research hypothesis will be tested using the structural equation method, namely SEM (Structural Equation Modeling) with an alternative method, namely PLS (Partial Least Square). The results of processing boostraping data, Student activity with learning achievement of 0.328 has a high influence (F-square value close to 0.35). The competence of lecturers with learning achievement of 0.063 has a relatively low influence. Learning motivation with learning achievement of 0.294 has a moderate influence.